Association of liver function and prognosis in patients with severe fever with thrombocytopenia syndrome. - Shaoqiu Zhang; Jian Wang; Qun Zhang; Yifan Pan; Zhiyi Zhang; Yu Geng; Bei Jia; Yuanyuan Li; Yali Xiong; Xiaomin Yan; Jie Li; Huali Wang; et al. (Public Library of Science (PLoS), 2024)
Objectives Severe fever with thrombocytopenia syndrome (SFTS) is an epidemic emerging infectious disease with high mortality rate. We investigated the association between liver injury and clinical outcomes in patients with SFTS. Methods A total of 291 hospitalized SFTS patients were retrospectively included. Cox proportional hazards model was adopted to identify risk factors of fatal outcome and Kaplan-Meier curves were used to estimate cumulative risks. Results 60.1% of patients had liver injury at admission, and the median alanine transaminase, aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin (TBil) levels were 76.4 U/L, 152.3 U/L, 69.8 U/L and 9.9 μmol/L, respectively. Compared to survivors, non-survivors had higher levels of AST (253.0 U/L vs. 131.1 U/L, P < 0.001) and ALP (86.2 U/L vs. 67.9 U/L, P = 0.006), higher proportion of elevated ALP (20.0% vs. 4.4%, P < 0.001) and liver injury (78.5% vs. 54.9%, P = 0.001) at admission. The presence of liver injury (HR 2.049, P = 0.033) at admission was an independent risk factor of fatal outcome. Conclusions Liver injury was a common complication and was strongly associated with poor prognosis in SFTS patients. Liver function indicators should be closely monitored for SFTS patients.